Hazardous material and chemical, biological, radiological, and nuclear incident readiness among prehospital care professionals in the State of Qatar. Issue 1 (31st December 2022) - Farhat, Hassan; Laughton, James; Gangaram, Padarath; El Aifa, Kawther; Khenissi, Mohamed Chaker; Zaghouani, Ouissem; Khadhraoui, Moncef; Gargouri, Imed; Alinier, Guillaume
ABSTRACT: This study aimed to determine whether the Hamad Medical Corporation Ambulance Service (HMCAS) personnel fulfil the pre-hospital readiness requirements for hazardous material and chemical, biological, radiological, and nuclear (HazMat-CBRN) incidents. This cross-sectional study performed an online assessment of non-specialist paramedics' behaviour and knowledge about HazMat-CBRN incident management, followed by a 'HazMat-CBRN incident management' course with pre-and post-activity assessments. The validity and reliability of the knowledge assessment questions were also tested. The pre-and-post course assessement responses revealed certain deficiencies in staff knowledge. The multiple linear regression and paired groups t -test demonstrated that this was rectified after the training intervention. The results indicate that the implemented course helped HMCAS staff acquire a satisfactory level of knowledge to ensure their readiness for safe and effective responses to potential HazMat-CBRN incidents in Qatar.